Using stable nitrogen and oxygen isotopes to identify nitrate sources in the Lancang River, upper Mekong. (15th November 2020) - Guo, Xiaojuan; Tang, Yongchun; Xu, You; Zhang, Sisi; Ma, Jun; Xiao, Shangbin; Ji, Daobin; Yang, Zhengjian; Liu, Defu
Abstract: The Lancang River in China is the headwater of the Mekong River. The impacts of reservoirs on the water, sediment and nutrient trapping in the Lancang River have attracted considerable attention, both locally and abroad. In this research, watershed-scale nitrogen load and nitrate sources along the Lancang River upstream in free-flowing reaches (FFRs) and downstream regulated reaches (RRs) were analyzed using stable nitrogen and oxygen isotopes. The results showed that the nitrogen nutrient (TN, NO3 − and NH4 + ) concentration increased from upstream to downstream along the Lancang River, and the highest values come from large-scale urban samples rather than the reservoirs. Compared to other large rivers in China, such as the Yangtze River, Yellow River and Yalu Tsangpo River, nitrogen nutrient content in the Lancang River is at low level. The nitrate concentration ranged from 0.14 mg/L to 0.63mg/Land increased significantly downstream. The isotopic values ranged from 2.8‰ to 5.2‰ for δ 15 N–NO3 - and from 4‰ to 8.5‰ for δ 18 O–NO3 - along the river, and the δ 15 N–NO3 - value rose significantly downstream. According to the nitrogen and oxygen isotope approach, soil organic nitrogen mineralization was the main source of the nitrate with an average of 51% contribution; domestic sewage was the second largest contributor with an average of 33% but increase downstream, likely due to the significantly larger population in the downstream region. Furthermore, the nitrate concentration decreased and δ 15 N- and δ 18 O–NO3 - enriched in the Nuozhadu reservoir, indicating that the reservoir may enhance nitrate consumption and reduce nitrogen pollution to downstream reaches. The results provide a perspective of nitrogen nutrient for the trans-border river management and more insight researches are called for understanding the controversial nutrient transport topic in this region. Graphical abstract: Image 1 Highlights: Isotopic values of δ 15 N and δ 18 O of nitrate in Lancang River are reported. Concentration and δ 15 N-NO3 − increased downstream, mainly controlled by increasing population and anthropogenic activities. Soil organic nitrogen mineralization and domestic sewage are the main sources of nitrate. Nitrate was consumed and δ 15 N- and δ 18 O–NO3 - were enriched in the reservoir.